2010
DOI: 10.1371/journal.pone.0014001
|View full text |Cite
|
Sign up to set email alerts
|

Iron Deficiency and Acute Seizures: Results from Children Living in Rural Kenya and a Meta-Analysis

Abstract: BackgroundThere are conflicting reports on whether iron deficiency changes susceptibility to seizures. We examined the hypothesis that iron deficiency is associated with an increased risk of acute seizures in children in a malaria endemic area.MethodsWe recruited 133 children, aged 3–156 months, who presented to a district hospital on the Kenyan coast with acute seizures and frequency-matched these to children of similar ages but without seizures. We defined iron deficiency according to the presence of malaria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 30 publications
2
25
0
3
Order By: Relevance
“…Regarding the presence of iron deficiency anemia in group A and group B, anemia was diagnosed in 72.0% of group A while in group B anemia was diagnosed in 50.0% there was statistical significant difference between group A and group B presence of iron deficiency anemia with OR of 2.57, 95% CI (0.90-7.34) .These results agree with Singh et al, who found that IDA was 1.9 times more common with patients of febrile convulsion this has also been reported by Idro et al, [17,18]. In Raju and Kumar Iron deficiency was found to be a significant risk factor for Febrile seizures in children of age group 6 months to 5 Years with (P value 0.0008) [9].…”
Section: Discussion:-supporting
confidence: 88%
“…Regarding the presence of iron deficiency anemia in group A and group B, anemia was diagnosed in 72.0% of group A while in group B anemia was diagnosed in 50.0% there was statistical significant difference between group A and group B presence of iron deficiency anemia with OR of 2.57, 95% CI (0.90-7.34) .These results agree with Singh et al, who found that IDA was 1.9 times more common with patients of febrile convulsion this has also been reported by Idro et al, [17,18]. In Raju and Kumar Iron deficiency was found to be a significant risk factor for Febrile seizures in children of age group 6 months to 5 Years with (P value 0.0008) [9].…”
Section: Discussion:-supporting
confidence: 88%
“…Daod et al Piscane et al and Fallah et al also found serum ferritin to be statistically correlating with febrile seizures. 13,19,27 Vaswani et al, Kumari et al among Indian studies have reported the same correlation between febrile seizures and serum ferritin levels. 17,20 In studies by Bidabadi et al, Yousefchaijan et al and Idro et al, patients did not show any statistical correlation between ferritin levels and febrile convulsions.…”
Section: Discussionmentioning
confidence: 64%
“…17,20 In studies by Bidabadi et al, Yousefchaijan et al and Idro et al, patients did not show any statistical correlation between ferritin levels and febrile convulsions. 20,22,28 Piscane et al also showed that IDA was 1.9 times more common with patients of febrile convulsion this has also been reported by Idro et al and Fallah et al 13,27,28 Numerous studies have addressed the association between iron deficiency anaemia and febrile seizure in children both in India and abroad. The results, however, have been controversial and even primary researches with high number of cases have failed to provide unequivocal results.…”
Section: Discussionmentioning
confidence: 78%
“…Exclusion criteria consisted of receiving a zinc combination or supplementation within the past 2 mo, central nervous system infections, history of previous febrile or afebrile seizure, neurodevelopmental delay, presence of any chronic systemic diseases (endocrine, cardiac, renal, metabolic, malignancy, rheumatologic, etc), iron deficiency, and iron deficiency anemia (anemia was defined as hemoglobin level of less than 10.5 g/dL in 18 mo to 2 y and less than 11.5 g/dL in 2 to 6 y and iron deficiency was defined as serum ferritin level of less than 12 ng/mL if CRP was negative or 1þ, ferritin level of less than 30 ng/mL if CRP was !2þ, or serum iron levels of less than 22 mg/dL) [12].…”
Section: Methodsmentioning
confidence: 99%